Analisa Sistem Pengendalian Penjualan Dan Pengaruhnya Terhadap Efektivitas Penjualan - Hasibuan, David HM; Supardji, Supardji (Jurnal Ilmiah Ranggagading (JIR), 2012)
Selling control system is one of important things in influencing selling effectiveness in a company. Therefore, the selling system implemented in the company, both cash and credit system, is not independent from the influence of the control system applied in the company. Effective control system can provide a huge influence to the companyâs selling effectiveness. The purpose of this study is to analyze how the selling control system is applied in the company and its impact to the companyâs selling effectiveness, to find out if the control system applied has been effective and has positive impact on the companyâs selling effectiveness. The research was conducted by the author at Setia Tapioca Factory, located in Bogor. The results show that the selling control system implemented by Setia Tapioka Factory has been effective as seen from continuousincreasing sales over the last five years, even exceeding the target of selling volume increase from 2007 until 2011. Thereafter, the achievement of payment target of sale accounts receivable as high as 95% can be fully collected or paid well.In conjunction with the repayment period average of sale accounts receivable, 75% has been paid less than 30 days. And there is no corruption done by the employees. The conclusion is the selling system applied in Setia Tapioca Factory has been effective, even thouh there are still some shortcomings such as no separation of duties in heading financial and accounting records (the two is headed by one person), no separation of functions between warehouse and expedition, and a salesman chief still does service in credit authorization as well. The weaknesses should be overcome by the company in order to improve the selling control system in Setia Tapioca factory.